Tradisi Mamakiah serta Dampaknya Terhadap Internal dan Eksternal Kelembagaan Pondok Pesantren - Niimmasubhani, Niimmasubhani (Institut Darul Quran Payakumbuh, 2014)
Abstract This article discusses about the influence of mamakiah on the internal dan exsternal institution of boarding school Pondok Pesantren Nurul Yaqin Ringan-ringan Pakandangan Kabupaten Padang Pariaman.This problem is based by the different interpretation on the hadits of shadaqah. According to several modernists, those hadits prohibit begging activities including mamakiah. In fact, however, there are some boarding schools still assign their students to collect fund by begging or mamakiah. Actually, there are some reasons why they ask their students to do that. The first one is due to the students’ financial problem. Next, the tradition is regarded phylosophical values like; sufistic, da’wah, and psychological values.This research is purposed to : (1)to know the nature and short history of mamakiah, (2) to explain about the form, technique, and phylosophy, (3) to study the effect of mamakiah on the internal institution of Pondok Pesantren Nurul Yaqin, and (4) to tell the effect of mamakiah on the external institution Pondok Pesantren Nurul Yaqin.